2011
DOI: 10.1016/j.ajhg.2011.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants at 13q12.12 Are Associated with High Myopia in the Han Chinese Population

Abstract: High myopia, which is extremely prevalent in the Chinese population, is one of the leading causes of blindness in the world. Genetic factors play a critical role in the development of the condition. To identify the genetic variants associated with high myopia in the Han Chinese, we conducted a genome-wide association study (GWAS) of 493,947 SNPs in 1088 individuals (419 cases and 669 controls) from a Han Chinese cohort and followed up on signals that were associated with p < 1.0 × 10(-4) in three independent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 28 publications
2
50
1
Order By: Relevance
“…The present study and many previous studies supported the observations that -Refractive errors are multifactorial with genetic and environmental factors and interaction between them, as well as -parental history of refractory error is an important risk factor for its development such as Chalasani et al, Kathrotia [25][26][27][28][29][30][31][32][33] In the present study it was found that cases have more reading hours per week (17.37) as compared to controls (11.11) and this difference in means of reading hours per week was found statistically significant (p<0.001). Similar finding was observed by Wakode et al…”
Section: Discussionsupporting
confidence: 77%
“…The present study and many previous studies supported the observations that -Refractive errors are multifactorial with genetic and environmental factors and interaction between them, as well as -parental history of refractory error is an important risk factor for its development such as Chalasani et al, Kathrotia [25][26][27][28][29][30][31][32][33] In the present study it was found that cases have more reading hours per week (17.37) as compared to controls (11.11) and this difference in means of reading hours per week was found statistically significant (p<0.001). Similar finding was observed by Wakode et al…”
Section: Discussionsupporting
confidence: 77%
“…Twin studies add further support, indicating heritability values between 0.5 and 0.90 (9)(10)(11). Genome-wide association studies have identified putative gene loci on chromosomes 13q (12) and 15q (13,14), as well as genetic variants in CTNND2, as being associated with myopia (15). Recently, a missense variant in LEPREL1 (encoding prolyl 3-hydroxylase 2 [P3H2]), a 2-oxoglutarate-dependent dioxygenase that hydroxylates collagen molecules, was associated with an autosomal-recessive form of high myopia and early-onset cataracts in an Israeli-Bedouin kindred (16).…”
Section: Introductionmentioning
confidence: 83%
“…Furthermore, genetic variants at 4q25 and 13q12.12 were revealed to be associated with high myopia in Han Chinese population. 10,11 Treating refractive error as a quantitative trait, Soluki et al 12 and Hysi et al 13 each discovered a locus for myopia at 15q14 and 15q25 in populations of European descent, respectively.…”
Section: Discussionmentioning
confidence: 99%